2022
DOI: 10.1101/2022.09.12.22279779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of long-term sequelae by cardiopulmonary exercise testing 12 months after hospitalization for critical COVID-19

Abstract: BackgroundCardiopulmonary exercise testing (CPET) is an important clinical tool that provides a global assessment of the respiratory, circulatory and metabolic responses to exercise which are not adequately reflected through the measurement of individual organ system function at rest. In the context of critical COVID-19, CPET is an ideal approach for assessing long term sequalae.MethodsIn this prospective single-center study, we performed CPET in 60 patients, 12 months after a critical COVID-19 infection that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…A French study carried out a cardiopulmonary test 12 months after hospitalization for COVID-19 (23) and found VȮ 2 values within normal limits in 80% of their sample, but reported ventilatory ine ciency, which corroborates the behavior of V̇E throughout the period, similarly to our study.…”
Section: Figure 1 Heresupporting
confidence: 89%
See 2 more Smart Citations
“…A French study carried out a cardiopulmonary test 12 months after hospitalization for COVID-19 (23) and found VȮ 2 values within normal limits in 80% of their sample, but reported ventilatory ine ciency, which corroborates the behavior of V̇E throughout the period, similarly to our study.…”
Section: Figure 1 Heresupporting
confidence: 89%
“…However, there remains a dearth of evidence concerning the assessment of functional capacity using eld tests combined with gas analysis in this population. Furthermore, most studies examining long COVID have focused on evaluating patients up to 6 months (20,21) and 12 months post-infection (22,23) following the acute phase. Few studies have ventured into assessing the functional capacity and QoL in this population beyond the two-year mark since the onset of the acute disease.…”
Section: Figure 1 Herementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies have reported persistent pulmonary symptoms in patients without persistent physiologic impairments [39,40]. One study aimed to investigate the long-term pulmonary effects of severe COVID-19 pneumonia by assessing cardiopulmonary exercise test (CPET) performance in 60 patients 12 months after a COVID-19 infection that required ICU management [41]. Exercise capacity assessed by CPET was within normal limits in most patients 12 months after hospitalization, and impairment was predominantly related to persistent deconditioning or prior respiratory comorbidities.…”
Section: Plos Onementioning
confidence: 99%